2019
DOI: 10.1111/eje.12480
|View full text |Cite
|
Sign up to set email alerts
|

Self‐perceived preparedness of undergraduate dental students in dental public universities in Malaysia: A national study

Abstract: Aims:To evaluate the self-perceived preparedness of final-year dental undergraduate students in dental public universities in Malaysia. Methods:Final-year dental undergraduate students from six dental public universities in Malaysia were invited to participate in an online study using a validated DentalUndergraduates Preparedness Assessment Scale DU-PAS. Results:In total, about 245 students responded to the online questionnaire yielding a response rate of 83.05%. The age range of the respondents was 23-29 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(61 citation statements)
references
References 23 publications
17
43
0
1
Order By: Relevance
“…Nevertheless, there were several areas of weakness that require improvement especially those related to evidencebased practice. This conforms with studies performed in different worldwide institutions where evidencebased dentistry and critical appraisal skills were lacking [14,24,26,27]. We can still argue that the attitudes and knowledge of graduates may alter after embarking into the career world and their concerns might be overcome once they integrate into their practice.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, there were several areas of weakness that require improvement especially those related to evidencebased practice. This conforms with studies performed in different worldwide institutions where evidencebased dentistry and critical appraisal skills were lacking [14,24,26,27]. We can still argue that the attitudes and knowledge of graduates may alter after embarking into the career world and their concerns might be overcome once they integrate into their practice.…”
Section: Discussionsupporting
confidence: 85%
“…Our results show that self-perceived preparedness for graduating students was satisfactory for a wide range of affective skills and traits. Our students showed con dence in communication and continuous development, similarly to other studies [22,23,24,25]. Nevertheless, there were several areas of weakness that require improvement especially those related to evidencebased practice.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with studies from other medical sub-fields [21][22][23]. It is possible that students have difficulty reading scientific papers, and this can be attributed to several factors, including unfamiliar terminology or research techniques in scientific papers, difficulty understanding statistics, having to wade through numerous papers to find the information, and inadequate training to identify the clinical application of knowledge gained from scientific journal articles [22,24]. Earlier studies have also stated that dental students lack resources for retrieving evidence-based information, which is a barrier for moving into this direction [13][14][15].…”
Section: Discussionsupporting
confidence: 83%
“…The range of the TPS for all the participants is 69-120 from a 0-120 scale with a mean of 97.2 is considered satisfactory and slightly higher than what Yudine (2019) reported about the self-perceived preparedness of undergraduates dental students in Malaysia, where they found a total score ranges from 48-100 from a 0-100 scale with a mean score of 79.56. 23 . Differences in TPS were noticed between the classes.…”
Section: Discussionmentioning
confidence: 99%
“…Those results suggest that dental graduates of University of Jordan are well prepared to perform the basic general dentistry procedures and that their general con dence is very good and comparable to the other dental schools around the world. 7,23,26,27 Around 60% of the participants reported that COVID-19 had some to severe impact on the level of con dence in performing general dentistry procedures. The lockdown that happened due to COVID-19 lead to almost two months loss of performing general dentistry.…”
Section: Discussionmentioning
confidence: 99%